Географія виборів в об’єднаних територіальних громадах: загальні тенденції й партійні впливи - Козак, Тарас; Kozak, Taras (My University, 2017)
Проаналізовано формування первинних адміністративно-територіальних одиниць в умовах децентралізації. Окреслено дезінтеграційні процеси в новостворених громадах. Відображено загальну суспільно-географічну характеристику місцевих виборів в об’єднаних територіальних громадах. Виявлено регіональні особливості електоральної поведінки населення. Висвітлено роль політичних партій у територіально-політичній системі України. Latest geopolitical realities of the Ukrainian society (eurointegration processes, revolutions, military conflict) clearly determined the disbalance in formation of territorial party-political system. It’s obvious seen in the fact that the total vector of political parties impact doesn’t enable the balance to entire national and regional interests. So, among the political and geographical research it is necessary to conduct complex monitoring and analysis concerning social and geographical problems to improve the political sphere. Impact reflection through the prizm of political forces will allow to determine territorial structure of the state in space and time. In the article we have: analysed the formation of primary administrative and territorial units under conditions of decentralization; described disintegrational processes in newly-formed communities; reflected general social and geographical characteristics of local elections in the united territorial communities; discovered regional peculiarities of electorial behaviour of the population; showed the role of political parties in the territorial and political systems of Ukraine.
Geography of Elections in United Territorial Communities: General Tendences and Party Influences
Keywords: геополітичні виклики; місцеві вибори; об’єднана територіальна громада; політична партія; партійний вплив; електоральна поведінка; geopolitical challenges; local elections; united territorial community; political party; party influence; electorial behaviour